Vad är teknik? Pedagogers uppfattningar om och erfarenheter av teknik och teknikundervisning i förskolan What is technology? Preschool teachers' conceptions and experiences of technology and technology education in the preschool - Helene Elvstrand; Jonas Hallström; Kristina Hellberg (Nordina: Nordic Studies in Science Education, 2018)
In recent years technology has become increasingly emphasized as educational content in the Swedish preschool, not the least with the introduction of the latest curriculum in 2010 (revised in 2016). Since preschool teachers have not had any formal technology education until just recently, it is of importance to investigate how they conceive of and experience technology in the daily activities of the preschool. The purpose of this study is therefore to describe and analyze Swedish preschool teachers’ views and experiences of technology and technology education in the preschool, focusing on what opportunities and obstacles that they see. The data consists of transcripts from focus group interviews with sixteen teachers in two Swedish preschools, and the data was coded and categorized with a thematic analysis. The results show that when it comes to opportunities, the teachers consider technology to permeate all preschool activities, and the challenge here is rather to make technology visible. In terms of obstacles, however, the teachers are also uncertain about what technology is and want to have more knowledge of technology themselves, for example, relevant concepts for various technologies or activities. They also want to know more about technology education in order to be able to educationally convey knowledge of technology to the children and to make the children conscious of the technology that surrounds them.